Caracterização dos produtores inseridos na ovinocultura de São Sepé - RS: do lazer ao lucro - Scherer, Cibele Bolzan (2015)
The transformations that have marked the rural areas reflected in a new era productive. What once used to empirical methods to produce, he won a differentiated performance with the arising of industrial Brazil. So the producers went through to the technological moment and the field became targeted as a place to generate income and working hours, until then been seen often as subsistence and housing. However, these changes that emerged over the course of nearly four decades and is recognized as the New Rural Brazilian period, also generated problems such as rural exodus by the exclusion of small producers that did not fit to productive manner and as soon as the city became be attractive by offering jobs generated by the urbanization of the country. Parallel to this phenomenon, the state's sheep industry, which contributed to the historical formation of the southern fields with meat supply to the resorts and the commercialization of wool that yielded profits for the maintenance of property, passed her time of crisis with the entry of synthetic wool in the domestic market, which led producers to direcionarem its production profile of sheep meat and the improvement of lambs for sale. Thus, while Brazil urbanizava up and acquired technology, gaucho producers lost property to the city and properties in short, give up the sheep production. However, what we see is that even after the implementation of management techniques and the profit motive, there are still properties that keeps the same sheep flock without commercial purposes. This paradigm we tried to unravel along this research in order to characterize the producers of São Sepe-RS and determine the purpose of production in profit or pleasure, since it distinguishes the choices in producing for the sale of lambs and production to only consumption of the property. Thus, one can determine the production methodology dedicated to entertainment and a way to produce historical review on sheep. However, what one sees is the lack or poor characterization of this way of thinking in rural areas as opposed to leisure is only seen the what is done in off hours and on rare occasions given Beheerder an emotional bond itself the history of every human being.